Impact of the full-scale war in Ukraine on the environment: Environmental damage assessment - Yu. Polukarov; N. Kachynska; O. Polukarov; O. Zemlyanska; L. Mitiuk (Law. Human. Environment)
The full-scale invasion of the Russian Federation has threatened not only the sovereignty and integrity of Ukraine but also the state of the environment, as military operations have a direct impact on the quality of natural resources, which makes this topic relevant. The study aims to determine the impact of the war on the state of the environment in Ukraine, as well as on the environmental rights of citizens. The methods used in the study included statistical, legal hermeneutics, induction, comparative methods, and others. The study results are the essence of environmental protection and the main components of this category, namely, soil, land, water resources, atmosphere, and biodiversity. The author clarifies the essence of the environmental rights of Ukrainian citizens and what they consist of, as well as how they can be violated. It is pointed out that in the context of military confrontation, Ukrainians are limited in their ability to stay in an environment that is safe for health and life. An estimate of the environmental damage caused by the hostilities is provided, which amounts to $59.7 billion, but is not entirely accurate or definitive, given the obstacles to data collection and lack of access to the occupied territories. The most common negative consequences of military operations and the environmental damage they cause are illustrated, examines in more detail such an environmental crime as the destruction of the Kakhovka hydroelectric power plant, and provides an estimate of material damage to various sectors, as well as the impact on the environment in the region. The differences between the Ukrainian methodology for assessing environmental damage and the American and European ones are noted. The article emphasises the need to take into account international recommendations and the use of the latest technologies to collect data on the long-term consequences of environmental damage caused by a full- scale invasion. The results of the study can be used for further work and practical improvements to the methodology for assessing environmental damage by lawyers and environmentalists